SWK-05. Clinical social work in pediatric neuro-oncology – A research project on the social dimension using social diagnostics. (3rd June 2022) - Krottendorfer, Kerstin; Rosenmayr, Verena; Weiler-Wichtl, Liesa Josephine; Pletschko, Thomas; Peyrl, Andreas; Leiss, Ulrike
Abstract: PURPOSE: A neuro-oncological disease of a child represents a high psychosocial burden for the whole family (Wiener, Kazek et al. 2015). A biopsychosocial and family-oriented approach for the treatment of children and their families focusing on medical, psychological and social care is significant in the course of the disease. Studies show that existential problems or lack of social support are risk factors. Therefore, this research investigates the impact of a pediatric neuro-oncological disease on the social dimension using a standardized social assessment. RESEARCH DESIGN: The project is based on a retrospective cross-sectional study (04/2015-12/2021) including consecutive patients with high- or low-grade gliomas at the Medical University of Vienna - Department of Pediatrics (n= 160). By using a specialized and standardized social diagnostic tool (DISAPO) starting at the onset of disease, the clinical social worker surveys the social situation (social network, work situation, financial and housing situation, legal status, insurance status, etc.) with the parents. Based on the assessed social situation the clinical social work interventions (CSWI) are recorded throughout the child′s treatment. The results are statistically evaluated including medical data. RESULTS: The results of the DISAPO show that in the course of the disease all families need CSWI in one or more areas of the social dimension: disease-related interventions: 100%, work intervention: 80, 6% (n=129), living situation: 43, 8% (n=70), social support: 39, 4% (n=63), socioeconomic interventions: 19, 4% (n=31), residence law aspects: 18, 8% (n=30). CONCLUSION: These results emphasize that in case of a pediatric neuro-oncological disease the social dimension is always affected and comprehensive CSWI are highly needed. For a holistic care of the patients and their families a biopsychosocial standard-of-care including all professions is indispensable. In addition, a standardized approach for assessment and intervention showed that needs could be assessed more adequately and interventions more targeted.